(untitled) (Research, Society and Development, 2021)
Facial volumetric appearance is defined by bone structures and soft tissue. Among these structures, the Bichat ball has received special attention for significantly influencing the contour of the middle third of the face. It is a fatty structure, located in the cheeks, which can be surgically removed for aesthetic and functional purposes, contributing to facial harmony and reducing traumatic lesions in the cheek mucosa. Bichectomy, an intraoral surgery for partial resection of the Bichat ball, has been frequently requested in dental office, and it is important for the professional to be trained so that the procedure can be successful. Therefore, the aim of this study was to report the surgical technique based on a clinical case, in which the patient presented aesthetic complaints, due to the greater volume in the middle third of the face, and functional complaints, due to the chronic nibbling of the cheek mucosa bilaterally. After surgery, there was a reduction in the volume of the cheeks and improvement in the patient’s facial contour, in addition to no longer nibbling on the mucous membranes, proving that, when properly indicated, the surgery achieves the expected results.